The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00128-007-9320-6
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and Distribution of Mercury and Other Heavy Metals in Surface Sediments of the Yatsushiro Sea including Minamata Bay, Japan

Abstract: The concentrations and distribution of heavy metals, such as mercury, zinc, copper, lead, and iron in surface sediments from 234 stations of the Yatsushiro Sea including Minamata bay were investigated. High concentrations of mercury were found in sediments from Minamata bay and its vicinity, but the levels decreased gradually with distance from the bay. The concentrations of mercury in sediments decreased gradually from south to north of the Yatsushiro Sea. These imply the lack of movement of mercury from Mina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
(19 reference statements)
1
12
1
Order By: Relevance
“…5). Moreover, the total Hg concentration in the surface sediment in Minamata Bay (Nakata et al 2008) and in the SS observed here was similar, as discussed in Section 3.3. Based on these results, assuming that the physicochemical properties of SS near the sea bottom are uniform, and that some part of the diss-THg is derived from resuspended sediment, we obtain a partial explanation of our observations regarding the bottom sea layer.…”
Section: Influences Of Ss Characteristics and Particulate-thg On The supporting
confidence: 84%
See 1 more Smart Citation
“…5). Moreover, the total Hg concentration in the surface sediment in Minamata Bay (Nakata et al 2008) and in the SS observed here was similar, as discussed in Section 3.3. Based on these results, assuming that the physicochemical properties of SS near the sea bottom are uniform, and that some part of the diss-THg is derived from resuspended sediment, we obtain a partial explanation of our observations regarding the bottom sea layer.…”
Section: Influences Of Ss Characteristics and Particulate-thg On The supporting
confidence: 84%
“…1 Seawater sampling sites in Minamata Bay tion. Tomiyasu et al (2008) characterized the geographical distribution of Hg concentrations in the bottom sediment and bottom seawater, and Nakata et al (2008) studied the distribution of total Hg concentrations in surface sediments in Minamata Bay. Only Logar et al (2001) reported the seasonal variations, vertical distribution, and solid/liquid partitioning of Hg in the water column of Minamata Bay.…”
mentioning
confidence: 99%
“…Nakata et al [79] investigated concentrations and distribution of heavy metals, such as Hg, zinc, copper, lead, and iron in surface sediments from 234 stations of the Yatsushiro Sea including Minamata bay. High concentrations of Hg were found in sediments from Minamata bay and its vicinity, but the levels decreased gradually with distance from the bay.…”
Section: Mercury Contaminated Sites Inmentioning
confidence: 99%
“…Recently, Snyder (2012) 9) mentioned that the Asahi Shinbun reported that between January 2005 and June 2010 around 568 people who live in the designated area for relief measures in Amakusa region, the western part of Yatsushiro Sea, plus 160 people who live outside of the designated area have shown similar symptoms with Minamata Disease patients 9) . Another evidence of mercury transport from Minamata Bay to the Yatsushiro Sea was reported by Nakata et al (2008) 10) . They observed in the Yatsushiro Sea, the background Hg concentration in sediment from 0.1 ppm has increased to more than 0.4 ppm, especially in the southern part of Yatsushiro Sea 10) .…”
Section: Introductionmentioning
confidence: 92%
“…Another evidence of mercury transport from Minamata Bay to the Yatsushiro Sea was reported by Nakata et al (2008) 10) . They observed in the Yatsushiro Sea, the background Hg concentration in sediment from 0.1 ppm has increased to more than 0.4 ppm, especially in the southern part of Yatsushiro Sea 10) . By those reports above, it can be assumed that the sediment transport still occurs from remaining Hg concentration in Minamata Bay to the Yatsushiro Sea even after the dredging and reclamation projects.…”
Section: Introductionmentioning
confidence: 92%